2019
DOI: 10.1111/jpi.12588
|View full text |Cite
|
Sign up to set email alerts
|

MTNR1B loss promotes chordoma recurrence by abrogating melatonin‐mediated β‐catenin signaling repression

Abstract: Chordoma is an extremely rare malignant bone tumor with a high rate of relapse.While cancer stem cells (CSCs) are closely associated with tumor recurrence, which depend on its capacity to self-renew and induce chemo-/radioresistance, whether and how CSCs participate in chordoma recurrence remains unclear. The current study found that tumor cells in recurrent chordoma displayed more dedifferentiated CSC-like properties than those in corresponding primary tumor tissues. Meanwhile, MTNR1B deletion along with mela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…Drp1-related mitochondrial fission is regulated by multiple mechanisms [110][111][112][113]. In NAFLD, p53 induces Drp1-related mitochondrial fission and mitophagy arrest, which results in mitochondrial dysfunction through mPTP opening, reduced mitochondrial potential, oxidative stress, calcium overload, and ATP depletion [109].…”
Section: Agingmentioning
confidence: 99%
“…Drp1-related mitochondrial fission is regulated by multiple mechanisms [110][111][112][113]. In NAFLD, p53 induces Drp1-related mitochondrial fission and mitophagy arrest, which results in mitochondrial dysfunction through mPTP opening, reduced mitochondrial potential, oxidative stress, calcium overload, and ATP depletion [109].…”
Section: Agingmentioning
confidence: 99%
“…Mao et al 40 found that MLT inhibited EMT and migration in breast cancer through disturbing the AKT-Ser473/GSK-3β-Ser9/β-catenin/SNAIL axis. Liu et al 41 showed that MLT inhibited β-catenin activation and stemness in chordoma through decreasing the phosphorylation level of Y86/Y333/Y654 residues in β-catenin. Chao et al 42 found that MLT decreased EMT and metastasis in lung cancer through targeting the β-catenin/TWIST axis.…”
Section: Discussionmentioning
confidence: 99%
“…Chordoma is a rare malignant bone tumor with a high recurrence rate. 30 The characteristics of the growth mode and location of chordoma make it difficult to completely remove the tumor. Due to the chemical resistance of chordoma, the clinical effects of radiotherapy and chemotherapy are unsatisfactory because there is no effective drug treatment.…”
Section: Discussionmentioning
confidence: 99%